Mandiocultura, produção do espaço e pequena produção familiar no município de Lagarto/SE - Souza, ítala Santana (2011)
This study examines the changes in/of the cassava culture in the city of Lagarto-SE, as well as its repercussions on the production of space and on the reproduction of the families which work with that activity. For this study achievement 70 questionnaires were applied, divided by the villages of Açu Velho, Açuzinho, Colônia Treze, Brasília and Boa Vista do Urubu, and secondary information gathering about the municipal livestock census and agricultural production regarding various years and also literature review on the theme. From an analysis based on the explanation of how the space is being produced by human actions and of how it constitutes a force field whose energy is the social dynamic, it was observed that the rural space in Lagarto city is marked by the contradictory insertion of money. However, in the reality of the villages which were visited it can be noticed, concomitantly to this fact, the progress of the production units based on family labor. In the study area, these units stand in cultivation, especially of cassava, a product that has been expanding for more than a decade at the detriment of other traditional cultures in the city, such as oranges and tobacco. Thus, it is considered that the money monopolizes the territory of Lagarto city and appropriates the family units surplus, redefining, from the production, both social and productive relations. On the other hand, the small family farmers look for some ways to stay in the field through diversification of production, from planting other crops such as acerola and passion fruit (products of easy acceptance on the market), from the sale of their temporary workforce either in or outside agriculture, a factor that confirms the strength of those beings in the creation and recreation regarding the forms of resistance on the soil.